VR-Based Workplace Training and Spaces of Learning: A Social Space Study of VR Training for Apprentice Electricians - Kraus, Katrin; Berger, Martin; Keller, Thomas; Brucker-Kley, Elke (International Journal for Research in Vocational Education and Training, 2025)
Context: This study uses a social space approach to investigate Virtual Reality (VR)-based workplace learning in the context of apprenticeship training in the electronics industry in Switzerland. It was one part of a project which developed a prototype VR environment that enables apprentices to practice testing an electrical installation in a virtual garage using VR headsets. The study uses a spatial theory perspective to understand how the apprentices use the VR environment to develop their vocational competence and how spaces of learning are created through this process. Approach: The study applies a socio-spatial perspective to a triangulation of the results of a qualitative content analysis of structured interviews with 16 apprentices and their 11 trainers and a quantitative analysis of a close-ended apprentice survey questionnaire (N = 16). Results: When a VR environment is used for workplace learning, spaces of learning are created from the interplay of four spatial dimensions: The regulation and practices of use of the VR environment, the locality of use, the educational potential of the VR environment, and a mental representation of the real workplace represented in the VR environment. The VR headset acts as a boundary object in the training relationship. Other important findings of the study are: Automated access to learning opportunities reduces pressure on the teaching-learning relationship; the haptic dimension of work is important for competence development; the VR environment enables personalized learning with unlimited opportunities for practice; the lack of variety in the operational scenario enables apprentices to focus on practicing and perfecting procedures but does not reflect the complexity of the real world. Conclusion: Our socio-spatial analysis shows that when VR environments are used in workplace training the interplay of physical, mental, and virtual spatial dimensions leads to the emergence of learning spaces. The access to the VR environment, the location where it is used, and the active use of its learning features interact with the mental representations of the depicted environment. Spaces of learning created using a VR environment can complement traditional workplace training by facilitating the development of specific aspects of vocational competence.